Hubungan Infeksi Soil Transmitted Helminth dengan Status Gizi Balita di Desa Tesabela, Kabupaten Kupang, Nusa Tenggara Timur - Meliance Bria; Yuni Elvira Seo (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Helminthiasis infection is one of the diseases that still occurs in the surrounding community. One type of helminthiasis disease that results in infection is the STH worm. Nutritional status problems are commonly encountered in various provinces of Indonesia which results in the quality of oneself for the future will be affected. The purpose of this study was to determine the relationship between helminthiasis infections and nutritional status in toddlers based on anthropometric measurements using weight and height indices. The type of research used is descriptive with a Cross sectional research design. Data that has been collected from 62 patients was described to link STH infection with Nutritional Status in Toddlers. The results of the study stated that there was no relationship between Soil Transmitted Helminth infection and gisi status in toddlers in Tesabela Village, West Kupang District with chis-quare test results, obtained a value of P=0.953 (P>a0.05).